Building the knowledge society on the Internet sharing and exchanging knowledge in networked environments - Bolisani, Ettore, 1963- (Hershey, PA : Information Science Reference, 2008)
'In today's networked societies, a key factor of the social and economic success is the capability to exchange, transfer, and share knowledge. This book provides research on the topic providing a foundation of an emerging and multidisciplinary field'--Provided by publisher.
'Premier reference source'--Cover.
Description based on print version record.
Includes bibliographical references (p. 358-395) and index.
Keywords: Knowledge management; Computer networks; Information networks; Electronic books; Electronic books